PENGARUH KOMPENSASI DAN JOB INSECURITY TERHADAP TURNOVER INTENTION PADA BURUH DI KABUPATEN KUDUS (STUDI KASUS PADA PT. PURA BARUTAMA UNIT OFFSET DIVISI PRODUKSI) - Farizka Ayuningtyas; Hari Susanta Nugraha (Universitas Diponegoro, 2018)
Human resources is an important factor in the company as it can support the achievement of goals in the company. Hence, the company must maintain human resources in order not to leave the company and find work in other companies. So to suppress human resources especially laborers out of the company (turnover intention) the company should pay attention to the factors that support turnover intention, including compensation and job insecurity factors. This study aims to determine the effect of compensation and job insecurity on turnover intention in case study at PT. Pura Barutama Unit Offset Production Division. This type of research using explanatory research and sampling technique using nonprobability sampling technique with purposive sampling method, data collection technique using questionnaire method. The number of samples used in this study as many as 100 respondents. This research uses quantitative and qualitative analysis with validity test, reliability test, correlation coefficient, coefficient of determination, regeresi sedehanand multiple test, and significance of T and F test. The results of this study indicate that the compensation and job insecurity variables have a strong influence on turnover intention variables. The compensation variable has a strong influence as well as the direction of negative relationship to the turnover intention variable. While job insecurity variables have a very strong influence and have a positive relationship direction to the variable turnover intention.